Information Systems in Business: A Literature Study on Management Opportunities in Information Technology - Ratih Septyanti (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2023)
Management constitutes a structured means of organizing, controlling, and regulating human resources to accomplish organizational objectives. It is indispensable for both personal and business purposes. When conducted systematically, management enables businesses to expand effectively and to adopt sound policies. In the digital era, however, the challenges of change management have become increasingly complex as advances in information and communication technology permeate nearly all aspects of human life. Consequently, it is necessary to identify the challenges and opportunities of change management in digital contexts and to adopt updated conceptual approaches grounded in technological progress. This study provides a qualitative literature review that synthesizes contemporary perspectives on information-technology–driven management practices. The findings aim to assist readers in understanding management concepts in information technology and their implications for organizational transformation and competitive performance.